FACE THREATENING ACTS (FTAs) IN AIPAC POLITICAL ANNUAL SPEECHES BETWEEN 2006 AND 2012 - Tarak Dridi (LLT Journal: A Journal on Language and Language Teaching, 2021)
Face Threatening Acts are politeness forms which have been struggled over in the past and now as they are pragmatically deemed relevant in identifying centripetal and centrifugal movements exerted by political actors on their interlocutors.  The findings on approaching political discourse from politeness perspective have been controversial and ranged from being confined to the interactional level to negotiating implicit power relations.This present study offers a politeness theoretical framework to examine AIPAC political annual speeches between 2006 and 2012.  The target of this research is to understand which politeness strategies political actors deploy when addressing the audience and how these political speakers please the other and fulfill political ends.  The results display an over-reliance on Face Threatening Acts on record with redressive action at the expense of Face Threatening Acts on record without redressive action and Face Threatening Acts off record.  Positive politeness, notably expressive speech acts, play an inclusive role, gain the audience sympathy and reshape public opinion.  The study fills the gap in the study of the impact of positive politeness on political discourse and calls for the consideration of expressive speech acts as means of power negotiation rather than mere interaction.